CIRCULAR ECONOMY IN THE AGRICULTURAL SECTOR: AN ANALYSIS OF THE LITERATURE ON RESOURCE AND WASTE MANAGEMENT - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The circular economy in the agricultural sector presents an innovative approach to address the challenges of sustainable resource and waste management. Utilising the concept of recycling and reusing agricultural waste, this approach aims to optimise the efficiency of resources such as soil, water, energy, and organic matter. The results of agricultural waste management in the form of compost, biogas and biomass can add value to the farm itself and related industries, while reducing negative impacts on the environment. This literature review highlights that technologies such as biotechnology and smart farming, as well as collaborative policies, are crucial to accelerate the implementation of the circular economy in the agricultural sector. However, challenges such as limited access to technology, high initial costs, and lack of education among farmers are major obstacles in the transition towards a more circular system. Therefore, synergy between the government, research institutions, private sector, and the community is needed to create infrastructure, incentives, and education that support the implementation of this concept. Thus, circular economy in the agricultural sector has the potential to be a strategic solution to create a more efficient, environmentally friendly, and sustainable agricultural system.